2006
DOI: 10.1124/jpet.105.100149
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Metabolites Induce an Endothelial Nitric Oxide-Dependent Vasorelaxation through Their Antioxidative Property-Independent Mechanisms: Possible Involvement of the Metabolites in the Antihypertensive Effect of Sesamin

Abstract: Sesamin, a major lignan in sesame seeds and oil, has been known to lower blood pressure in several types of experimental hypertensive animals. A recent study demonstrated that sesamin metabolites had in vitro radical-scavenging activities. Thus, we determined whether the antioxidative effect of sesamin metabolites modulate the vascular tone and contribute to the in vivo antihypertensive effect of sesamin. We used four demethylated sesamin metabolites: SC-1m (piperitol), SC-1 (demethylpiperitol), SC-2m [(1R,2S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 30 publications
5
80
0
Order By: Relevance
“…Our preliminary test showed that this compound induced a relaxation on aorta precontracted with noradrenaline (results not shown). This finding has also been reported by Nakano et al (2006), who suggested that the enhancement of endotheliumdependent vasorelaxation induced by sesamin metabolites is one of the important mechanisms of the in vivo antihypertensive effect of sesamin. Moreover, it has been demonstrated that T. africanus contains some terpenoid compounds (Kimbu et al, 1984;Ayafor et al, 1994).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our preliminary test showed that this compound induced a relaxation on aorta precontracted with noradrenaline (results not shown). This finding has also been reported by Nakano et al (2006), who suggested that the enhancement of endotheliumdependent vasorelaxation induced by sesamin metabolites is one of the important mechanisms of the in vivo antihypertensive effect of sesamin. Moreover, it has been demonstrated that T. africanus contains some terpenoid compounds (Kimbu et al, 1984;Ayafor et al, 1994).…”
Section: Discussionsupporting
confidence: 69%
“…A recent study demonstrated that sesamin and its metabolites had in vitro radical scavenging activities (Nakano et al, 2006). This compound (sesamin, a lignan) and terpenoids present in T. africanus extract may be responsible in part for its antioxidative activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought that sesamin may improve hypertension by its ability to induce nitric oxide and inhibit endothelin-1 production from human umbilical vein endothelial cells ( 25 ). Furthermore, it is suggested that the metabolic products had potent radical-scavenging activities in vitro ( 2 ) and that the enhancement of endotheliumdependent vasorelaxation induced by sesamin metabolites is one of the important mechanisms of the in vivo antihypertensive effect of sesamin ( 31 ). Taken together, it is considered that sesamin might involve several pathways in its hypotensive effects ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lignans are natural antioxidants present in sesame oil. Lignans have health benefits, including antioxidant activity [25], anticarcinogenic [26], blood pressure-lowering [27] and serum lipid-lowering [28]. Table 3 depicts the data for the moisture, fat, protein, carbohydrates, ash, crude fiber, oryzanol, and lignans.…”
Section: Resultsmentioning
confidence: 99%